The world meets Asian tourists - Pearce, Philip L.; Wu, Mao-Ying (Bridging tourism theory and practice ;, 2016)
The movement of Asian citizens across continents now occurs on an unprecedented scale, with a surge in Asian tourists now visiting Europe, North America, Africa and Oceania. Tourists from China, Taiwan, India, Thailand, Malaysia, and to a lesser extent Korea and Japan are meeting the citizens of cultures they had previously only been able to read about or view from afar. This book seeks to understand the experiences of, and reactions to, Asian tourists travelling out of Asia.Questions about Asian tourist contact with unfamiliar countries and cultures will be addressed. What are the interests of Asian tourists and what drives these interests? What impacts are they having on host communities, both in terms of the provision and co-creation of desired experiences and in the human dimensions of social contact? The volume addresses fresh implications for marketing, planning and policy which these tourist markets pose for good governance. This book confronts the limitations of our understanding of how to manage the tourist experience when that understanding has been built almost entirely on the behaviours and travels of western tourists.